Ozonetherapy as a supporting in the treatment of periodontitis: literature review (Research, Society and Development, 2021)
Introduction: Periodontitis is characterized as a chronic and multifactorial inflammation that is related to biofilm imbalance. The gold standard in therapy is through periodontal scaling, generally supported by an association of common and systemic antibiotics. However, drugs can lead to the development of bacterial resistance or patient discomfort. Thus, ozone therapy has stood out as a form of adjuvant intervention for the disease and the inflammatory process. Objective: To demonstrate, based on the literature, the efficiency of ozone therapy as an adjunct in the treatment of periodontitis. Methodology: A search in Pubmed, Embase, Scopus, Web of Science (all databases), and Cochrane Library databases was performed using a search strategy based on the MeSH terms “periodontitis”, “ozone” and “inflammation” and their corresponding input terms. No additional search filters were added. Only articles with their full text published and dealing with periodontitis as the primary focus of the study were included. Data were obtained through a qualitative synthesis of the results. Results and Discussion: 21 articles were selected and similar designs varied. All articles are emphatic about the safe use of ozone therapy, however, they differ as to its real practical effect in the clinic. Studies are still not conclusive about the expected effect. Conclusion: Despite its anti-inflammatory effects, ozone therapy does not seem to have a significant effect as periodontal treatment, but it can be used as an auxiliary measure in difficult-to-control cases in which periodontal scaling alone does not present satisfactory results.